2015
DOI: 10.1371/journal.pone.0126357
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Malic Enzyme and ATP-Citrate Lyase in Non-Small Cell Lung Cancer of the Young and the Elderly

Abstract: BackgroundLung cancer is the leading cause of death among malignancies worldwide. Understanding its biology is therefore of pivotal importance to improve patient’s prognosis. In contrast to non-neoplastic tissues, cancer cells utilize glucose mainly for production of basic cellular modules ‘(i.e. nucleotides, aminoacids, fatty acids). In cancer, Malic enzyme (ME) and ATP-citrate lyase (ACLY) are key enzymes linking aerobic glycolysis and fatty acid synthesis and may therefore be of biological and prognostic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…Hanai et al () indicated that ACL deficiency is correlated with MET, differentiation and apoptosis in NSCLC (A549), leading to the inhibition of tumor growth in vivo. Clinically, ACL was also found to be upregulated and associated with local tumor stage, suggesting a prognostic value on NSCLC (Csanadi et al, ). It is therefore possible that the ATP concentration can significantly affect the biological behaviors of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Hanai et al () indicated that ACL deficiency is correlated with MET, differentiation and apoptosis in NSCLC (A549), leading to the inhibition of tumor growth in vivo. Clinically, ACL was also found to be upregulated and associated with local tumor stage, suggesting a prognostic value on NSCLC (Csanadi et al, ). It is therefore possible that the ATP concentration can significantly affect the biological behaviors of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Both ME and ATP-citrase lyase (ACLY) are enzymes related to aerobic glycolysis and fatty acid synthesis. They are both correlated with NSCLC cells, and ACLY tends to be more localized, whereas ME tends to signify mediastinal lymph nodes, a site of metastasis in the human body [34]. Interestingly, in young patients, overexpression of ACLY and/or ME correlated with extended survival compared to patients who did not overexpress ACLY and/or ME.…”
Section: Mitochondrial Respiration and Biogenesis Genes Are Upregulatmentioning
confidence: 96%
“…Furthermore, some of the genes that were found to be upregulated in smokers were upregulated more depending on how frequently the smoker smoked. Malic enzyme (ME) expression is also significantly increased in the lung tissues of smokers compared to nonsmokers [34]. The EGFR pathway is the most common signaling pathway for lung cancer, and the mutation rate of genes of the EGFR pathway reach 70-80% [32].…”
Section: Mitochondrial Respiration and Biogenesis Genes Are Upregulatmentioning
confidence: 99%
“…In this study a total of 79 subjects with tumours of the ocular adnexa who had been treated at the Eye Center of Freiburg University between 1995 and 2012 were included. Clinical data, such as histological diagnosis, age at diagnosis, gender, treatment modality, follow-up time, local recurrences, metastasis and/or death, were collected on each subject from patient charts, primary care physicians and the Clinical Tumour Registry of the Medical Center at the University of Freiburg [6]. As some of the patients had already died at the time of this retrospective analysis, we could not obtain informed consent from all patients.…”
Section: Patientsmentioning
confidence: 99%